Pembangunan Hukum yang Mengakomodir Pluralisme di Indonesia - La Ode Angga (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Pluralism, a popular diversity, is not only an attitude of acknowledging and accepting a reality of pluralistic society, but also a sincere attitude to accept the reality as a positive value, as the grace of God to mankind. Therefore, it will enrich the cultural growth through the dynamic interaction and cross-diverse cultural exchanges. Pluralism is a way to push the nation's cultural enrichment. Indonesian culture or "keindonesiaan" is nothing but a result of resourceful and dynamic interaction among the diverse actors in an effective melting pot. Plurality is a diversity based on virtue (uniqueness), and distinctiveness. Hance, the existence of plurality can not be realized or imagined except as an antithesis and a comparative object of uniformity and unity encapsulating its dimensions. This paper will explore the uniqueness of Indonesian law.